Marketing Strategy for CLEANANDSHINE (Peofessional Shoes Treatment) - Deo Saputra, Mochamad; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2017)
Abstract. Cleanandshine is a business engaged in the field of cleaning and care service for all kinds of shoes. Cleanandshine was founded by M Deo Saputra, Fajar Hidayat, and Rangga Adiputra on April 5, 2016. This business located in Kelapa Dua, Depok and has three types of services that cleaning service, repair service and repaint service. The problems faced by Cleandandshine is the absence of the portion of work in marketing function. Function marketing this not see well by the company from the marketing marketing strategy until marketing implementation itself. This certainly affected sales and earnings company. In business exploration, the writer analyst external strategy by using PEST analysis, porter 5 forces analysis and competitive profile matrix (CPM) analysis. For Internal analysis, the writer uses marketing mix 7p and STP (Segmenting, Targeting, Positioning). The next items produced by that analysis is put in formulations strategies, so company using tools tows matrix. To classify these items, the strategy using by the writer is marketing mix 7P to show which strategy can be implement in the company to boost sales and revenue. The result of the analysis and tools shows that Cleanandshine is in the position of market followers and requires 15 marketing strategies the implementation to boost sales and income company. The marketing strategies built with plan implementation timeline strategy and also the budget The Company have to improve distribution sales places in online and offline. To increase sales and revenue, the company should make variations in product which is services or goods products also can be a solution to company to increase sales and revenue.Keywords: Marketing Strategy, Shoes Treatment, TOWS Matrix, CPM